Presurgery adhesion molecules and angiogenesis biomarkers are differently associated with outcomes in colon and rectal cancer: results from the ColoCare study - Ose, Jennifer; Gigić, Biljana; Hardikar, Sheetal; Lin, Tengda; Himbert, Caroline; Warby, Christy A.; Peoples, Anita R.; Lindley, Clara L.; Boehm, Juergen; Schrotz-King, Petra; Figueiredo, Jane C.; Toriola, Adetunji T.; et al. (Cancer epidemiology, biomarkers & prevention, 2022)
Cell-to-cell adhesion and angiogenesis are hallmarks of cancer. No studies have examined associations of adhesion molecules and angiogenesis biomarkers with clinical outcomes in colorectal cancer.In presurgery serum from n = 426 patients with colorectal cancer (stage I-III), we investigated associations of CRP, SAA, adhesion molecules (sICAM-1, sVCAM-1), and angiogenesis markers (VEGF-A and VEGF-D) with overall survival (OS), disease-free survival (DFS), and risk of recurrence. We computed HRs and 95% confidence intervals; adjusted for age, sex, BMI, stage, site, and study site, stratified by tumor site in exploratory analyses.N = 65 (15%) were deceased, and 39 patients (14%) had a recurrence after a median follow-up of 31 months. We observed significant associations of biomarkers with OS, DFS, and risk of recurrence on a continuous scale and comparing top to bottom tertile, with HRs ranging between 1.19 and 13.92. CRP was associated with risk of death and recurrence in patients in the top tertile compared with patients in the bottom tertile, for example, risk of recurrence HRQ3-Q1: 13.92 (1.72-112.56). Significant heterogeneity between biomarkers and clinical outcomes was observed in stratified analysis by tumor site for CRP, SAA, sICAM-1, sVCAM-1, and VEGF-D. VEGF-D was associated with a 3-fold increase in risk of death for rectal cancer (HRlog2: 3.26; 95% CI, 1.58-6.70) compared with no association for colon cancer (HRlog2: 0.78; 95% CI, 0.35-1.73; Pheterogenity = 0.01).Adhesion molecules and angiogenesis biomarkers are independent prognostic markers for colorectal cancer, with differences by tumor site.There is need for tailored treatment for colon and rectal cancer.